The theoretical feasibility of a physical exercise program for the rehabilitation of patients with cervical spinal injuries in Guinea-Bissau (Original) (Revista científica Olimpia, 2019)
Patients with spinal cord injuries may have loss of function in the trunk, lower extremities, motor and sensory loss in the arms and hands. The level of functioning in these people is, in most cases, determined by the deterioration of the arms and hands, so that these patients can be classified as incomplete spinal cervical lesions there must be at least preservation of the sensory function in the patients. S4-S5 segments, with no motor function below the neurological level of the lesion. These pathological states can improve if you perform a correct application of planned physical exercises, oriented, dosed and controlled in a systematic way. However, in Guinea-Bissau only drug treatments are used. For this reason it was determined to design a program of physical exercises for the rehabilitation of patients suffering from incomplete cervical spinal injuries. In the research the theoretical, analytic-synthetic, inductive deductive, historical-logical and systemic approaches, and empirical methods, document review and survey were used. As results, a program is presented that includes a general objective and five specific objectives, three stages with their specific objectives, methodological orientations, control and evaluation. The program was consulted with 19 experienced neurological rehabilitation specialists, 95% rated the indicators evaluated as very adequate and adequate. Therefore, it was concluded that the program was feasible and pertinent to be applied by specialists in neurorehabilitation with injured cervical spinal patients.
Keywords: neurorehabilitation, cervical spinal cord injury. therapeutic physical exercise